Legality Letter of Statement of Khilaf in Indonesia Criminal Justice System - Rugun Romaida Hutabarat (Fiat Justisia: Jurnal Ilmu Hukum, 2018)
In criminal law, a person charged with a criminal offense may be punished if it meets two matters, namely his act is unlawful, and the perpetrator of a crime may be liable for the indicated action (the offender's error) or the act may be dismissed to the perpetrator, and there is no excuse. The reasons may result in the death or the removal of the implied penalty. But it becomes a matter of how if the Letter of Statement Khilaf is the answer to solve the legal problems. The person who refuses or does not do what has been stated in the letters is often called "wanprestasi" because the statement is categorized as an agreement. The statement includes an agreement which is the domain of civil law or criminal law, so its application in the judicial system can be determined. This should be reviewed in the application of the law, are there any rules governing wrong statements in the criminal justice system. By using a declaration of khilaf as a way out of criminal matters, then the statement should be known in juridical rules. This study uses normative juridical methods, by conceptualizing the law as a norm rule which is a benchmark of human behavior, with emphasis on secondary data sources collected from the primary source of the legislation. The result of this research is that the statement of khilaf has legality, it is based on Jurisprudence No. 3901 K / Pdt / 1985 jo Article 189 Paragraph (1) of Indonesian criminal procedure law. However, this oversight letter needs to be verified in front of the court to be valid evidence, but this letter of error is not a deletion of a criminal offense, because the culpability of the defendant has justified the crime he committed. Such recognition, cannot make it free from the crime that has been committed.Keywords: Legality, Letter of Statement, Criminal Justice System